2013
DOI: 10.1177/1049909113486335
|View full text |Cite
|
Sign up to set email alerts
|

Training Mid-level Providers on Palliative Care

Abstract: Palliative care services are not available in most outpatient oncology practices. A program training 11 mid-level providers from oncology practices on advanced directive discussions and supportive symptom assessment and management performed by palliative care specialists was completed. A follow-up session 9 months later identified barriers to implementation. Of the 11 mid-level providers, 8 participated in the follow-up session, and 9 of the 11 providers implemented advanced directive’s discussions and symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…However, opportunities do exist to improve the delivery of supportive cancer care. In fact, studies have demonstrated that mid-level providers, after brief training, have been able to successfully screen patients for symptom burden and discuss end of life care [86], and should therefore be integrated into care programs. Trainees, including medical students, must have increased instruction in palliative and rehabilitation care.…”
Section: Advancing Collaborative Interdisciplinary Care Coordinationmentioning
confidence: 98%
“…However, opportunities do exist to improve the delivery of supportive cancer care. In fact, studies have demonstrated that mid-level providers, after brief training, have been able to successfully screen patients for symptom burden and discuss end of life care [86], and should therefore be integrated into care programs. Trainees, including medical students, must have increased instruction in palliative and rehabilitation care.…”
Section: Advancing Collaborative Interdisciplinary Care Coordinationmentioning
confidence: 98%
“…Earlier efforts to improve ACP focused on training nurses and other providers to have the knowledge, tools, and skills to initiate conversations about ACP (Lesperance et al, 2014). Curtis et al’s (2018) intervention expanded previous efforts by providing an individualized, patient-centered tool that prepares patients and their families (or other caregivers) to initiate conversations about ACP, thereby enabling patients to participate more actively and equally in communication and decisions about their health care.…”
Section: Introductionmentioning
confidence: 99%
“…Patient-related barriers occurred when the patient felt that engaging in such discussions was giving up hope; practice-related barriers were the lack of dedicated time for engaging in the conversation, and there were questionable reimbursement issues (Lesperance et al, 2014).…”
Section: Clinician Comfortmentioning
confidence: 99%
“…Clinician education and utilization of AD were illustrated in a study by Lesperance et al (2014). The main purpose of the study was to increase the knowledge of advanced practice nurses, physician assistants, and licensed clinical social workers on best practices related to the Five Wishes document in an oncology practice setting.…”
Section: Clinician Comfortmentioning
confidence: 99%